PVDF/MAF-4 composite membrane for high flux and scaling-resistant membrane distillation - Wu, Rui; Tan, Yanyan; Meng, Fangang; Zhang, Yuanyuan; Huang, Yu-Xi (Desalination, 2022)
Membrane distillation (MD) is promising desalination technology for hypersaline wastewater treatment. However, traditional MD membranes are subject to low vapor flux and mineral scaling. In this study, we report the fabrication of a composite membrane composed of polyvinylidene fluoride (PVDF) and metal azolate framework-4 (MAF-4) via electrospinning. The highly porous MAF-4 provides additional vapor transfer channels and better heat insulation, thereby significantly increasing the membrane flux compared to a bare electrospun PVDF membrane. The surface chemistry of the MAF-4 surface is further tailored with fluorinated functional groups through the coordination between the fluorinated molecule and the surface Zn atom. This surface modification changes the surface wettability of the MAF-4 and thus improves the membrane scaling resistance. This study demonstrates a universal approach for preparing high flux and scaling-resistant MD membranes. In addition, the tunable surface property of MAF-4 can also be utilized to design and fabricate other types of membrane surfaces by coordinating different functional molecules. •PVDF/MAF-4 composite membranes for membrane distillation were fabricated via electrospinning.•Membrane flux of the composite membrane was significantly improved due to the presence of MAF-4.•The composite membranes provided better vapor transfer kinetics and reduced the membrane thermal conductivity.•The surface of MAF-4 could be further modified with 3,5-bis(trifluoromethyl)benzoic acid to achieve better scaling resistance.